Kerjasama Indonesia – Malaysia dalam Menanggulangi Penyalahgunaan dan Perdagangan Gelap Narkoba 2009-2013 - Suproboningrum, Lintang; Utama, Tri Cahya; Rosyidin, Mohamad (Journal of International Relations, 2015)
This research seeks to explain bilateral cooperation between Indonesia and Malaysia against transnational drugs trafficking from 2009 to 2013. Using the neoliberal institutionalist theory, this research focuses on the driving force behind the policy as well as the effectiveness of the cooperation. In the era of globalization characterized by the development of technology and information that has a big impact on the relationship between countries, transnational crimes become commonplace. One of salient transnational crimes is drugs trafficking. Geographical proximity between Indonesia and Malaysia is one of the reasonsbehind drugs trafficking across borders of both countries. After collecting primary and secondary sources obtained from archival as well as literature research, this research found that the bilateral cooperation between Indonesia and Malaysia against drugs trafficking was influenced by the fear of the destructive impact of drugs on the youth. Both drugs abuse and drugs trafficking have been perceived as a threat by two countries, especially in terms of human security. This is because most of the drugs consumer is younger generation who is considered very crucial to the nation in the future. Indonesia and Malaysia alike were realized that drugs trafficking is a national security matter so they crafted a kind of international regime to achieve their national interest.Â